Disarmament Law : reviving the field (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This volume seeks to start a revival of the field of disarmament law scholarship. Law is a fundamental component of disarmament, yet today, most perspectives on the wide range of disarmament issues that exist come primarily from political, diplomatic and public advocacy angles. The aim of this book is to revive the field of disarmament law building on earlier, important and still relevant contributions by international lawyers to the subject. The collection brings together international scholars on various aspects of disarmament. The contributions range across a variety of weapons types, adopt different approaches - doctrinal, historical and critical - to the issues being discussed and taken together, constitute a snapshot of the ideas, concerns and issues that currently occupy disarmament law scholars. The book will be essential reading for academics, researchers and policy-makers working in the area of disarmament.
6 Addressing Victim Suffering Under Disarmament Law: Rights, Reparations and Humanising Trends in International Law -- Part III: Making Disarmament Law -- 7 Article 18 of the Vienna Convention on the Law of Treaties Obligations and the Comprehensive Nuclear-Test-Ban Treaty -- 8 Not a Love Affair: The Relationship Between the Treaty on the Prohibition of Nuclear Weapons and the Nuclear Non-Proliferation Treaty -- 9 The OSCE: A Study of the Role of 'Soft Law' in Disarmament -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Nuclear disarmament; Nuclear nonproliferation; Arms control; LAW / General; LAW / Air & Space; LAW / International